DNA Barcoding of Commercially Important Groupers (Epinephelidae) in Simeulue and Banyak Islands, Aceh, Indonesia - Fadli, Nur; Razi, Nanda Muhammad; Damora, Adrian; Muchlisin, Zainal A.; Ramadhaniaty, Mutia; Rahayu, Sri Riska; Harnelly, Essy; Habib, Ahasan; Siti-Azizah, Mohd Nor (Bogor Agricultural University, Indonesia, 2025)
The groupers are a group of demersal fish that live in tropical and subtropical areas and are mostly linked to coral reefs. The fish are highly valued in international markets and are subjected to overfishing in the wild. Accurate fish resource identification knowledge is essential for sustainable fisheries management. This research is aimed to generate a reference COI sequence library of grouper species caught in Simeulue and Banyak Islands, Aceh. The study was conducted from April-September 2021 at sixteen fish landing sites in Simeulue and Banyak Islands. In total, this study generated 70 COI sequences representing 20 grouper species. Epinephelus (54%) was the most prevalent grouper genus at the study site, followed by Cephalopholis (19%), Plectropomus (13%), Variola (12%), Hyporthodus (1%), and Anyperodon (1%). According to the IUCN classification, 17 species (85%) fall into the category of Least Concern, two (10%) fall into the category of Vulnerable, and one (5%) falls into the category of Data Deficient. The average genetic distance based on the Kimura-2-Parameter (K2P) between specimens was 0.51% at the species level and 8.34% at the genus level. Overall, this study has provided the COI sequence database of grouper for the Simeulue and Banyak Islands.